2014
DOI: 10.1097/jcp.0000000000000082
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Genetic Polymorphisms in the κ-Opioid Receptor 1 Gene With Body Weight, Alcohol Use, and Withdrawal Symptoms in Patients With Methadone Maintenance

Abstract: Methadone is a synthetic opioid that binds to the κ-opioid receptor with a low affinity. This study tested the hypotheses that the genetic polymorphisms in the κ-opioid receptor 1 (OPRK1) gene region are associated with methadone treatment responses in a Taiwan methadone maintenance treatment (MMT) cohort. Seventeen single nucleotide polymorphisms (SNPs) in OPRK1 were selected and genotyped on DNA of 366 MMT patients. Six SNPs from rs7843965 to rs1051660 (intron 2 to exon 2) were significantly associated with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 33 publications
0
18
1
Order By: Relevance
“…This variant has previously been reported to be part of a risk haplotype accounting for higher alcohol use and withdrawal symptoms in patients on methadone maintenance. 34 However, in another study, no association was found with heroin and alcohol addiction. 35 Interestingly, a recent randomised, placebo-controlled clinical trial showed that the opioid receptor antagonist naltrexone decreases ICD symptom severity in patients with PD with ICD.…”
Section: Discussionmentioning
confidence: 90%
“…This variant has previously been reported to be part of a risk haplotype accounting for higher alcohol use and withdrawal symptoms in patients on methadone maintenance. 34 However, in another study, no association was found with heroin and alcohol addiction. 35 Interestingly, a recent randomised, placebo-controlled clinical trial showed that the opioid receptor antagonist naltrexone decreases ICD symptom severity in patients with PD with ICD.…”
Section: Discussionmentioning
confidence: 90%
“…Wang et al [66] reported that a kappa-opioid receptor 1 gene polymorphism is associated with alcohol use, among other things. …”
Section: Clinical Correlates Of Aud In Opioid Dependencementioning
confidence: 99%
“…OPRK1 is critical in drug addiction, and OPRK1 agonists have inhibitory effects on addictions to alcohol, cocaine and opiate (28). Furthermore, several genetic variants of OPRK1 have been associated with heroin addiction (8,29,30). Previous studies have indicated that heritable factors may be important in addictive behavior (8,31), and suggest that higher levels of OPRK1 promoter methylation may be associated with heroin addiction.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, several genetic variants of OPRK1 have been associated with heroin addiction (8,29,30). Previous studies have indicated that heritable factors may be important in addictive behavior (8,31), and suggest that higher levels of OPRK1 promoter methylation may be associated with heroin addiction. The results of the present study indicate that OPRK1 promoter methylation affects the propensity of individuals to exhibit addictive behaviors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation